Severe Hypokalemia in the Intensive Care Unit: Case Series on Potassium Correction Strategies and Clinical Outcomes (Jurnal Anestesi Perioperatif, 2025)
Hypokalemia is one of the electrolyte disorders that often occurs in intensive care units (ICUs), defined as a serum potassium concentration below 3.5 mmol/L. Its severity is classified as mild (3.0–3.4 mmol/L), moderate (2.5–3.0 mmol/L), and severe (
Keywords: Hypokalemia; intensive care unit; life threatening; potassium correction; prognosis sever